Family Allowances and Clearing Funds in France - Douglas, Paul H. (Quarterly Journal of Economics, 1924)
Introduction. The background out of which family allowances have developed. — I. Family allowances to governmental employees and by firms not affiliated with clearing funds. The payment of allowances for children of governmental employees, 252.—The adoption of this system by local governments, 253. — Family allowances on the railroads, 254. — Coal mines, 255. — II. The growth of clearing funds. — The beginnings of the clearing-fund movement in Grenoble, 257. — Extraordinary growth during 1920, 259. — Extent and scope of clearing funds, 260. — III. Allowances granted under the clearing funds. — Types of allowances given and amounts, 264. — Development of home visiting and social work, 265. — Degree to which allowances are adequate to meet extra expense occasioned by children, 267. — Ratio of allowances to pay-roll, 268. — IV. Further features of allowances, 269. — Rules concerning eligibility of worker and child for benefit, 270. — Practice as regards absenteeism, short time, and unemployment, 271. — V. Structure of the funds. — Trade vs. regional funds, 273. — Reasons for each, 274. — Tendency for regional funds to subdivide into federations of trade funds, 274. — Methods of allocating contributions to be made by the employers, 275. — Payment of allowances by firms or by funds, 280. — Payment to father vs. payment to mother, 281. — VI. The Bokanowski proposal, 284. — Sweeping features of proposed law, 285. — Opposition of employers prevented its enactment, 285. — The system imposed, however, on contractors for State work, 286. — State assistance to large families, 287. — VII. Why employers have introduced the system, 288. — Desire to avoid wage increases for all employees paramount reason, 289. — Attitude of trade unionists at first hostile, but has recently been modified, 292. — Organized labor wants to change system, not abolish it, 293.